2020
DOI: 10.1200/edbk_279129
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Landscape of Treatment in Acute Myeloid Leukemia

Abstract: The treatment of acute myeloid leukemia is evolving, with increased understanding of molecular pathogenesis allowing better risk stratification and development of new therapies. Tests to identify and drugs to target specific molecular abnormalities are improving remission rates and prolonging survival in patients with high-risk disease. Allogeneic hematopoietic stem cell transplantation remains an important curative therapy, with advances in donor availability and approaches to reduce transplant-related mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“… 9 As relapse is not the primary cause of death in patients with MDS undergoing alloHCT, the choice of conditioning intensity is currently dependent on the estimated ability of a patient to tolerate transplant-related toxicity. 26 AlloHCT remains the only curative therapy for MDS; however, given the median age at diagnosis, many patients will not be eligible for myeloablative approaches. 27 , 28 As it is now possible to determine the genomic basis of disease before and after transplantation, personalized approaches for alloHCT of patients with MDS are now conceivable with targeted strategies for those with detectable TP53 , RAS pathway (including FLT3 ), IDH and JAK2 mutations, immune augmentation, or other therapies potentially able to supplement the impact of chosen conditioning intensity to minimize relapse risk.…”
Section: Discussionmentioning
confidence: 99%
“… 9 As relapse is not the primary cause of death in patients with MDS undergoing alloHCT, the choice of conditioning intensity is currently dependent on the estimated ability of a patient to tolerate transplant-related toxicity. 26 AlloHCT remains the only curative therapy for MDS; however, given the median age at diagnosis, many patients will not be eligible for myeloablative approaches. 27 , 28 As it is now possible to determine the genomic basis of disease before and after transplantation, personalized approaches for alloHCT of patients with MDS are now conceivable with targeted strategies for those with detectable TP53 , RAS pathway (including FLT3 ), IDH and JAK2 mutations, immune augmentation, or other therapies potentially able to supplement the impact of chosen conditioning intensity to minimize relapse risk.…”
Section: Discussionmentioning
confidence: 99%
“…9 As relapse is not the primary cause of death in MDS patients undergoing alloHCT the choice of conditioning intensity is currently dependent on the estimated ability of a patient to tolerate transplant-related toxicity. 25 AlloHCT remains the only curative therapy for MDS, however given the median age at diagnosis many patients will not be eligible for myeloablative approaches. 26,27 As it is now possible to determine the genomic basis of disease before and after transplantation, personalized approaches for alloHCT of MDS patients are now conceivable with targeted strategies for those with detectable TP53 , RAS-pathway (including FLT3), IDH and JAK2 mutations, immune augmentation or other therapies potentially able to supplement the impact of chosen conditioning intensity to minimize relapse risk.…”
Section: Discussionmentioning
confidence: 99%
“…Probability result from differences in the biology of the leukemic blasts in older versus younger patients, or a combination of these factors [29,31], also has shown that elderly patients that show karyotype anomalies, especially those in the high-risk category, do not benefit from intensive chemotherapy [32,33]. us, the SC : daunorubicin combination seems to overcome the difficulties of two classic antineoplastics against AML, one of the most common types of leukemia in adults according to the American Society of Clinical Oncology [34]. e mechanism of protection and action of SC : daunorubicin is not known but it is known that an alternative treatment for AML, known as CAG, consists of a lowdose regimen of cytarabine, aclarubicin, and G-CSF [21].…”
Section: Journal Of Oncologymentioning
confidence: 99%